2013
DOI: 10.1039/c2sc21657d
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage and hydrodeoxygenation (HDO) of C–O bonds relevant to lignin conversion using Pd/Zn synergistic catalysis

Abstract: The development of chemical methods for the direct catalytic conversion of biomass to high value organic molecules is an area of increasing interest. The plant matter component known as lignin is a polymer consisting of aromatic rings that could provide a means of obtaining aromatic materials currently derived solely from petroleum. This report describes a bimetallic Pd/C and Zn catalytic system that can perform selective hydrodeoxygenation (HDO) of monomeric lignin surrogates as well as successfully cleave th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
212
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(218 citation statements)
references
References 17 publications
5
212
0
1
Order By: Relevance
“…One reason for the relatively low hydrogenation rate of 5-5′ dimer might be caused by its intramolecular hydrogen bonds that could hinder the attack of the catalyst. Parsell et al used Zn/Pd/C catalyst for HDO of guaiacylglycerol-b-guaiacyl ether under relatively mild condition, 423 K and 20.7 bar hydrogen pressure, got complete conversion and yielded two main aromatic products [36]. The β-O-4 linkage was effectively cleaved to aromatic fragments, and its alcohol oxygen on alkyl chains was subsequently removed with loss of aromatic groups.…”
Section: 9mentioning
confidence: 99%
“…One reason for the relatively low hydrogenation rate of 5-5′ dimer might be caused by its intramolecular hydrogen bonds that could hinder the attack of the catalyst. Parsell et al used Zn/Pd/C catalyst for HDO of guaiacylglycerol-b-guaiacyl ether under relatively mild condition, 423 K and 20.7 bar hydrogen pressure, got complete conversion and yielded two main aromatic products [36]. The β-O-4 linkage was effectively cleaved to aromatic fragments, and its alcohol oxygen on alkyl chains was subsequently removed with loss of aromatic groups.…”
Section: 9mentioning
confidence: 99%
“…The same was valid for HDO of vanillin which maximally gave 65% selectivity towards methylcyclohexane at 300 °C under 50 bar over Ni/SiO2-ZrO2 catalyst (Table 1, entry 16). The main product from vanillyl alcohol HDO is 1,4-dimethoxyphenol using ZnCl2 as a catalyst in methanol (Table 1, entry 17) [21]. Transanthole contains both propyl and methoxy substituents and it is easy to deoxygenate (Table 1, entry 18).…”
Section: Bond Monolignolmentioning
confidence: 99%
“…In this present study, alkali lignin has been subjected to subcritical water depolymerization reactions with the application of formic acid (FA) as capping agent and hydrogen source and 5 wt% palladium supported on carbon (Pd/C) as hydrodeoxygenation (HDO) catalyst at 265 °C, 6.5MPa. Pd/C has been used in literature for hydrodeoxygenation of bio-oils and oxygenates in alcohols [21] and a recent publications showed that Pd/C can be effective for deoxygenation of triglycerides in subcritical water with external hydrogen supply [22]. At first, the hydrothermal reaction of FA was investigated at the given reaction conditions to determine the influence of reaction time and the presence of Pd/C catalyst on its ultimate conversion according to the equation (1) [19];…”
Section: A Introductionmentioning
confidence: 99%